Population dynamics and digitalization: implications for COVID-19 data sources in South Africa—a scoping review - Akokuwebe, Monica Ewomazino; Palamuleni, Martin E.; Idemudia, Erhabor Sunday (Frontiers in Public Health, 2025)
ObjectivesThe study explores how humanity influences the development of digitalization on population dynamics during the changing times of the Covid-19 pandemic.MethodsA scoping review was conducted using PRISMA guidelines. Fifteen full-text articles were selected from 40 identified studies (2020–2023).ResultsThree themes emerged: (1) influence of humanity on the development of digitalization on population dynamics during changing times, (2) technical and ethical challenges, and (3) solutions to these challenges.ConclusionFindings highlight the need for new opportunities for distinctive technical and ethical challenges in creating larger digital databases for population dynamics and how these databases may contribute to the advancement of population fields.